LANDFORMS AROUND MT. RIISER-LARSEN, AMUNDSEN BAY, EAST ANTARCTICA - アニヤ, マサム; ハヤシ, マサヒサ; ANIYA, Masamu; HAYASHI, Masahisa (National Institute of Polar Research, 1989)
P(論文) Landforms recognized in the Mt. Riiser-Larsen (about 1150m above the surrounding sea level) area, Amundsen Bay, Enderby Land, East Antarctica, were described and presented in a geomorphological map compiled from the result of field work and aerial photographic interpretation. Major landforms, primarily of glacial and periglacial origin, include aretes, cirques, free faces, slopes covered with frost-shattered rock fragments, talus and/or tills, moraines at several levels, glacio-fluvial channels and ponds, and sorted patterned grounds (mostly polygons).The till fields are located at several levels. From their locations, lithogical compositions, and the relative degree of development of patterned grounds on them, two levels were recognized to have been laid by the continental ice sheets (C-I and II), while four levels were judged to have been left by alpine glaciers (A-I, II, III and IV). Based on the distribution of these tills, the glacial sequence was inferred, although in a relative sense, as from older to newer, C-I, C-II, A-I, A-II, A-III, and A-IV. At present, it appears that the glaciation is not very active in this area, as three remaining small alpine glaciers appear to have been stagnant or started retreating. departmental bulletin paper